The Impact of Digital Financial Inclusion on Bank Profitability: Evidence from Developing Countries - Abdul Aziz, Sumayyah; Abdul Razak, Lutfi; Slesman, Ly Y.; Abduh, Muhamad (Universitas Airlangga, 2024)
Objective: This study aims to evaluate the impact of Digital Financial Inclusion (DFI) on the profitability of banks in developing countries, by constructing a novel comprehensive DFI index and employing dynamic panel analysis. Design/Methods/Approach: The research involves a sample of 111 banks across nine developing nations from 2016 to 2020. A new DFI index was constructed to encapsulate both the access and usage dimensions of DFI, along with demographic and geographical considerations, using Principal Component Analysis (PCA). The empirical framework adopted a dynamic panel model, applying two-step system Generalized Method of Moments (GMM) estimators to analyze the data. Findings: The findings indicate a positive and significant relationship between DFI and bank profitability. This relationship highlights the beneficial impacts of DFI on the financial performance of banks within the studied contexts. Originality/Value: This research broadens the current understanding of Digital Financial Inclusion (DFI) by focusing on its impacts not only on bank stability but also on profitability and efficiency, areas not extensively covered by prior studies. Additionally, it contributes to the literature by integrating demographic and geographical dimensions into the construction of a comprehensive DFI index. This approach provides a nuanced understanding of DFI’s effects on bank profitability and represents a significant deviation from traditional studies that focus mainly on access and usage. Practical/Policy implication: Based on the findings, it is recommended that bank managers and financial service providers establish strategic partnerships to strengthen the integration of traditional banking with digital financial services, thereby boosting bank profitability. Regulators must update policies to foster an environment that supports the integration of digital innovations, while ensuring robust consumer protection and data privacy standards. Continuous investment in digital infrastructure and financial literacy is crucial, alongside rigorous policy monitoring and adaptation, to maintain a regulatory framework that promotes the sustainable expansion of DFI and addresses emerging security challenges.